2022
DOI: 10.1073/pnas.2117364119
|View full text |Cite
|
Sign up to set email alerts
|

Food web rewiring drives long-term compositional differences and late-disturbance interactions at the community level

Abstract: Significance Multiple anthropogenic disturbances affect the structure and functioning of communities. Recent evidence highlighted that, after pulse disturbance, the functioning a community performs may be recovered fast due to functional redundancy, whereas community multivariate composition needs a longer time. Yet, the mechanisms that drive the different community recovery times have not been quantified empirically. We use quantitative food-web analysis to assess the influence of species interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 81 publications
4
7
0
Order By: Relevance
“…Furthermore, the recovery of energy flux (a proxy for interaction strengths) was negatively correlated with compositional recovery (Figure 4 ). In other words, if total energy flux increase over time, community composition will further depart from control conditions, supporting the hypothesis that changes in interactions strength are linked to compositional divergence (Polazzo, Marina, et al, 2022 ).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Furthermore, the recovery of energy flux (a proxy for interaction strengths) was negatively correlated with compositional recovery (Figure 4 ). In other words, if total energy flux increase over time, community composition will further depart from control conditions, supporting the hypothesis that changes in interactions strength are linked to compositional divergence (Polazzo, Marina, et al, 2022 ).…”
Section: Discussionsupporting
confidence: 55%
“…Consistently, both HW treatments significantly reduced compositional recovery, and community composition was significantly modified by both treatments at the end of the experiment. Previous studies have shown that changes in composition may allow a complete functional recovery after pulse disturbance (Hillebrand et al, 2018;Polazzo, Marina, et al, 2022). Complete functional recovery can be achieved because pulse disturbances may select for different compositions which can maintain functional level under disturbance if there is functional redundancy (Yachi & Loreau, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoplankton was not sampled in this experiment. We expect the phytoplankton species at the start of the experiment to be similar to previous studies performed with the same water source, including chlorophyta, cryptophyta, cyanobacteria, desmids, diatoms, dinophyta (Polazzo et al, 2022b;Polazzo et al, 2022a).…”
Section: Zoo-and Phytoplankton Sampling and Determinationsupporting
confidence: 60%
“…The concept that ecological network architecture can dynamically change in nature is central to our understanding of species coexistence in real ecological communities (21)(22)(23)(24)(25). If a food web has a fixed (rigid) network structure, extinction or population decline of a predator species may trigger the burst of the population size of some prey species, resulting in extinctions of competing prey species and subsequent cascade extinctions through the interaction network (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%